Entanglements of modernity, colonialism and genocide Burundi and Rwanda in historical-sociological perspective - Palmer, Jack Dominic (Classical and contemporary social theory, 2018)
This book offers a novel sociological examination of the historical trajectories of Burundi and Rwanda. It challenges both the Eurocentric assumptions which have underpinned many sociological theorisations of modernity, and the notion that the processes of modernisation move gradually, if precariously, towards more peaceable forms of cohabitation within and between societies. Addressing these themes at critical historical junctures - precolonial, colonial and postcolonial - the book argues that the recent experiences of extremely violent social conflict in Burundi and Rwanda cannot be seen as an 'object apart' from the concerns of sociologists, as it is commonly presented. Instead, these experiences are situated within a specific route to and through modernity, one 'entangled' with Western modernity. A contribution to an emerging global historical sociology, Entanglements of Modernity, Colonialism and Genocide will appeal to scholars of sociology and social theory with interests in postcolonialism, historical sociology, multiple modernities and genocide